Influência do design de restaurações endocrown em CAD/CAM na carga máxima de carregamento em molares tratados endodonticamente - Modena, Cláudia Freitas de Moura (2016)
Objectives: To evaluate in vitro the influence of different cavity design preparations for endocrown restorations on the fracture resistance of endodontically treated molars. Materials and methods: Fifty extracted healthy third molars were divided randomly into 5 groups (n= 10 per group): H= healthy, F1= 1 ferrule, F2= 2 ferrules (buccal and palatal), FT= total ferrule and NF= flat plateau. The teeth were submitted to root canal treatment after which the cavity preparations were made. The crowns of endocrown, in Lava Ultimate, were manufactured with the CAD-CAM CEREC/INLAB system and cemented with Single Bond Universal and Rely X Ultimate. The resistance to fracture testing was made in a universal testing machine with a speed of 1mm/min. The pattern of failure was then evaluated, taking into consideration only the presence or absence of fracture in the pulp floor. Results: (Means followed by the same letter do not differ statistically for ANOVA and Tukey): H:3970N ab; F1:3170N ab; F2: 3786N ab; TF: 2894N b; NF:4416N a. The most prevalent pattern of failure was the type recoverable in all groups. Conclusions: The type of cavity preparation for endocrown restoration may influence the fracture resistance of endodontically treated molars. The type of ferrule may determine the greater resistance to loading. The pattern of failure was predominantly recoverable.